Distribution. Russia (SE Siberia, including Transbaikalia), C & E Mongolia, and NC & NE China (Gansu, Inner Mongolia [= Nei Mongol], Ningxia, N Shaanxi, N Shanxi, Hebei, and Liaoning). in Muridae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Distribution. Russia (SE Siberia, including Transbaikalia), C & E Mongolia, and NC & NE China (Gansu, Inner Mongolia [= Nei Mongol], Ningxia, N Shaanxi, N Shanxi, Hebei, and Liaoning). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 648, DOI: 10.5281/zenodo.6887260 ...